2019
DOI: 10.1016/j.ejvs.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plaque Calcification and Stent Oversizing on Clinical Outcomes of Atherosclerotic Femoropopliteal Arterial Occlusive Disease Following Stent Angioplasty

Abstract: WHAT THIS PAPER ADDS Plaque calcification and stent oversizing have been confirmed as two key factors for in stent restenosis in atherosclerotic peripheral artery occlusive disease. An effective plaque scoring system and specific stent oversizing standard have been well established in the coronary artery. However, there are still no similar assessment methods for the femoropopliteal artery. In this study, automatic computer software was used to analyse the pre-operative computed tomography angiography (CTA) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This pathological response was believed to be due to the greater chronic outward force exerted by the stent on the wall in case of severe oversizing. Similar behaviour was observed in humans by He et al (2019) who analysed computer tomography (CT) angiography from patients affected with atherosclerotic femoropopliteal arterial occlusive disease, and demonstrated a positive correlation between severe oversizing (40% oversizing rate evaluated at the narrowest cross-sectional level of target lesion) and the incidence of ISR. Timmins et al (2011) combined in vivo analysis with computational methods to prove a strong correlation between the stress induced in the artery wall and the pathobiological response, which could likely culminate in neointimal thickening.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…This pathological response was believed to be due to the greater chronic outward force exerted by the stent on the wall in case of severe oversizing. Similar behaviour was observed in humans by He et al (2019) who analysed computer tomography (CT) angiography from patients affected with atherosclerotic femoropopliteal arterial occlusive disease, and demonstrated a positive correlation between severe oversizing (40% oversizing rate evaluated at the narrowest cross-sectional level of target lesion) and the incidence of ISR. Timmins et al (2011) combined in vivo analysis with computational methods to prove a strong correlation between the stress induced in the artery wall and the pathobiological response, which could likely culminate in neointimal thickening.…”
Section: Introductionsupporting
confidence: 74%
“…On the other hand, stent undersizing could lead to incomplete strut-to-artery apposition, which is recognized as a cause of stent thrombosis (Cook et al, 2012) and, in extreme cases, stent migration following implantation (Zhao et al, 2009). While it has been reported that incorrect sizing likely contributes to a proportion of the adverse clinical outcomes (Attizzani et al, 2014), a set of objective criteria to select the most appropriate stent diameter in peripheral settings have not yet been established (He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VC may cause arterial stiffness, luminal stenosis, and plaque instability ( Wu et al, 2016 ), which was an independent risk factor for morbidity and mortality of cardiovascular and cerebrovascular diseases (CCD) ( Bugnicourt et al, 2011 ; Leon and Maddox, 2015 ). VC could also limit complete expansion of a stent or balloon during interventional therapy ( He et al, 2019 ). VC was also associated with poor prognosis after revascularization ( Lee et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of a study, which of the following parameters are most closely associated with in-stent restenosis following femoropopliteal stenting? 4 A. A.…”
mentioning
confidence: 99%